OWNERSHIP OF A DENTAL OFFICE AS A FACTOR OF DENTAL TOURISM IN THE REPUBLIC OF NORTH MACEDONIA - Pavloska, Natasha (Journal of Morphological Sciences, 2021)
Dental tourism is considered as part of medical tourism and means travel abroad in order to receive dental services, which are usually more expensive in the home country. The Republic of North Macedonia with its geographical location is a current European destination for dental tourism. The study aimed to indicate certain experiences in the field of dental tourism in the Republic of North Macedonia according to the ownership of a dental office. This was a cross-sectional study conducted in the period from 15.02.2018 to 14.02.2019. The sample consisted of 215 dentists. A non-standardized questionnaire was used and applied with the Google Forms service. The responses of 215 dentists were analyzed; 131 (60.93%) were owners of a dental office and 84 (39.07%) were not owners of a dental office. There was no significant association between the ownership of a dental office and years of experience in working with foreigners, for Pearson Chi square = 5.05 and p> 0.05 (p = 0.28). There was a significant association between the ownership of a dental office and the statement of the share of foreigners in the total income of the office, for Pearson Chi square = 9.47 and p <0.05 (p = 0.04). A negative correlation was found between the answers to the analyzed questions and the number of dentists, depending on the ownership of the office. Keywords: dental tourism, ownership, dental office. https://doi.org/10.55302/JMS2143154p